2009
DOI: 10.1038/nm.2023
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of calpain increases LIS1 expression and partially rescues in vivo phenotypes in a mouse model of lissencephaly

Abstract: Lissencephaly is a devastating neurological disorder due to defective neuronal migration. LIS1 (or PAFAH1B1) was identified as the gene mutated in lissencephaly patients, and was found to regulate cytoplasmic dynein function and localization. Here, we show that more than half of LIS1 is degraded via calpain-dependent proteolysis, and that inhibition or knockdown of calpains protects LIS1 from proteolysis, resulting in the augmentation of LIS1 levels in Lis1+/− mouse embryonic fibroblast (MEF) cells, which lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
56
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 41 publications
2
56
0
Order By: Relevance
“…The calpain-calpastatin system has been shown to participate in a number of pathological conditions, including hypoxia, ischemia, spinal cord injury, Alzheimer's disease, muscular dystrophy, cataract, and lissencephaly (26,36,39). This is reflected in the finding that calpastatin deficiency enhances amyloidosis, inflammation, and neuronal atrophy in a mouse model of Alzheimer's disease (M. Higuchi and T. C. Saido, unpublished data).…”
mentioning
confidence: 97%
“…The calpain-calpastatin system has been shown to participate in a number of pathological conditions, including hypoxia, ischemia, spinal cord injury, Alzheimer's disease, muscular dystrophy, cataract, and lissencephaly (26,36,39). This is reflected in the finding that calpastatin deficiency enhances amyloidosis, inflammation, and neuronal atrophy in a mouse model of Alzheimer's disease (M. Higuchi and T. C. Saido, unpublished data).…”
mentioning
confidence: 97%
“…We recently demonstrated that inhibition or knockdown of calpain protects LIS1 from proteolysis resulting in the augmen tation of LIS1 levels in Lis1 +/-mouse embryonic fibroblast (MEF) cells, which leads to rescue of the aberrant distribution of cytoplasmic dynein and intracellular components including mitochondria and β-COP positive vesicles. 18 We also showed that presence of calpain inhibitors improves neuronal migration of Lis1 +/-cerebellar granular neurons. 18 This study demonstrates that stabilization of proteins in disorders caused by haploinsufficiency is a potential therapeutic strategy and provides a proof-of-principle for this notion.…”
mentioning
confidence: 61%
“…Although mNUDC is required for anterograde transport of a dynactin-containing complex, the dynein complex and the dynactin complex were separately transported to the plus end of MTs 9 . Interestingly, half of the LIS1 is degraded through calpain-dependent proteolysis at the plus end of MTs, and that inhibition or knockdown of calpains protects LIS1 from proteolysis, which leads to the rescue of the phenotypes in Lis1 þ / À mice 14 . Despite numerous studies for the regulation of motor proteins, the mechanism of LIS1 release from idling dynein at the plus end of MTs remains poorly understood.…”
Section: Normalized Intensity Of Immunoblotting Mt(-) Mt(-) Mt(+)mentioning
confidence: 99%